America’s perilous pivot - Solana, J (Oxford Institute for Energy Studies, 2013)
The Pacific or the Middle East? For the United States, that is now the primary strategic question. The violence in Gaza, coming as President Barack Obama was meeting Asia’s leaders in Phnom Penh, perfectly encapsulates America’s dilemma. Instead of being able to focus on US foreign policy’s ‘pivot’ to Asia, Obama was forced to spend many hours in conversation with the leaders of Egypt and Israel, and to dispatch Secretary of State Hillary Clinton from Asia, in order to facilitate a cease-fire in Gaza.